Helicobacter pylori IgM en pacientes diabéticos del Centro de Salud Universitario de Motupe - Erique Calero, Yeraldy Claribel (2025)
Diabetes mellitus that lasts for some time is responsible for the damage caused to various organs and systems; to the gastrointestinal system it causes diabetic gastroparesis, which delays and reduces gastric emptying and acid secretion, favouring bacterial overgrowth in the stomach, especially Helicobacter pylori. Approximately more than half of the world population is infected by this bacterium, and in Ecuador about 45% of the rural population and 47% of the urban population; being the females the ones with the highest rate. The purpose of this paper is to evaluate the serum levels of IgM against Helicobacter pylori in diabetic patients of the University Health Centre of Motupe; detailing the determination of serum levels of IgM against H. pylori by immunodiagnostic techniques (ELISA) and evaluating the presence of anti-H. pylori antibodies according to age, sex and time of diagnosis of diabetes mellitus. This was done by means of a cross-sectional analytical study, applied to 13 patients of both sexes between the ages of 42 to 80. The results obtained show that 53.8% of the patients have IgM antibodies against H. pylori; however, there was no statistically significant relationship between age, sex, time of evolution of diabetes and IgMH. pylori levels. Thus, we conclude that a higher percentage of diabetic patients have elevated levels of IgM against H. pylori, and although no statistically significant relationship was found between the variables, we can observe that most of the elevated results were found in the female population, those older than 66 years of age and those who had been ill for more than 10 years